ANALISIS PENERAPAN ETIKA BISNIS ISLAM DALAM MELAKUKAN TRANSAKSI DI PASAR TRADISIONALSTUDI KASUS DI PASAR PAGI PRUMDAM KOTA BENGKULU - Wati, Rudila; Dini, Ilka Gusrian (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study aims to fine out how Islamic Business Ethics is applied to buying and selling transaction in Prumdam market, Bengkulu City. The purpose of this study is to explore the understanding and application of Islamic Business Ethics among traders in Traditional markets. The main issue raised was the lack of understanding of traders regarding the principles of Islamic Business Ethics and the challenges they face. The study used a qualitative method with a descriptive approach, involving structured interviews with traders who had at least five years of experience in the Prumdam Morning Market. The results of the study show that some of the traders have understood the importance of honesty and Amanah in transactions, however there are some traders who are not effective in communicating the quality of the goods they sell, which reflects the lack of awareness of Islamic Business Ethics principles. Therefore, there is a need for better education and socialization to traders about Ethical values ​​which are the foundation in doing business.